2022
DOI: 10.1186/s12905-022-01671-8
|View full text |Cite
|
Sign up to set email alerts
|

Serum and gene expression profile of cytokines following combination of yoga training and vitamin D supplementation in breast cancer survivors: a randomized controlled trial

Abstract: Background This study aimed to examine the effect of the combination of yoga training with high vitamin D dose supplementation on the expression and systemic levels of inflammatory cytokines and psychophysical status of breast cancer survivors. Methods Thirty volunteered breast cancer survivors (48 ± 8 years) were randomly allocated to a high dose (4000 IU) of vitamin D supplementation (HD) group (n = 10), yoga with a high dose of vitamin D (YHD) g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…Several studies have found that the level of TNF-α is reduced in response to chemotherapy and that it correlates with treatment response [ 2 , 26 ]. A recent study showed that 12 weeks of yoga reduced TNF-α levels in breast cancer patients [ 27 ]. INF-γ was found to be higher in breast cancer patients than in healthy people in studies [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found that the level of TNF-α is reduced in response to chemotherapy and that it correlates with treatment response [ 2 , 26 ]. A recent study showed that 12 weeks of yoga reduced TNF-α levels in breast cancer patients [ 27 ]. INF-γ was found to be higher in breast cancer patients than in healthy people in studies [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the fold change of another inflammatory gene TNF-α was showing fluctuations and it significantly changed in the SC group at 2 and 4-week time points without modifying the IL- 6 at any time points. For IL-6 maybe in future studies, we should check the changes in abdominal fat content as it is correlated with abdominal fat deposition ( 65 ). It seems like inflammatory genes were not responding as they were intended to like in another similar study, in which 8 weeks of yoga-based lifestyle intervention significantly decreased the TNF-α and IL-6 expression in patients with rheumatoid arthritis ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…When compared to the identical training session performed in normoxia, their findings showed that team-sport athletes can perform an RSH session without increasing inflammation [80]. Another fascinating study looked at the impact of combining yoga with high vitamin D supplementation on the expression and systemic levels of inflammatory cytokines, as well as the psychophysical status of breast cancer survivors [81]. According to their findings, yoga improves physical and psychological fitness and, when combined with a high dose of vitamin D, improves cytokine profiles, which can help manage cancer-related side effects.…”
Section: Iht Mimicking High Altitude Adaptationmentioning
confidence: 99%